Association of genetic variants in chromosome 17q21 and adult-onset asthma in a Chinese Han population - Gong Yaoqin; Wang Aihua; Zhao Hailing; Fang QiuRong; Liu Qiji (BMC, 2011)
Abstract Background Genome-wide association studies of asthma have identified a novel region containing ORMDL3 at chromosome 17q21 that is strongly associated with childhood-onset asthma and significantly linked to ORMDL3 transcript abundance. These results have been successfully replicated in childhood-onset asthma cohorts in several ethnic groups. In this study, we aimed to evaluate the association of polymorphisms in ORMDL3, GSDMB, ZPBP2 and IKZF3 and adult-onset asthma in a Chinese Han population. Methods We genotyped 5 single nucleotide polymorphisms (SNPs) at chromosome 17q21 in 1,366 Han Chinese people comprising 710 patients with adult-onset asthma and 656 healthy controls. We compared the 2 groups in terms of allele and haplotype frequencies. Transcript levels were measured in leukocytes from 61 asthma patients by quantitative real-time PCR. Results We found the 5 SNPs significantly associated with asthma (P<0.05), of which 2, rs11557467 and rs9303277, were strongly associated (P<0.001). Subjects carrying the G allele of rs11557467 or the C allele of rs9303277 showed increased risk of asthma (odds ratio [OR] 1.27, 95% confidence interval 1.07-1.51, P = 0.006, and OR 1.27, 1.07-1.49, P = 0.005, respectively), even after adjusting for age and sex. The risk of asthma was lower for carriers of the haplotype CTGTT (OR 0.81, 0.67-0.97, P = 0.02). The risk allele for each SNP was associated with increased expression of ORMDL3 and GSDMB in leukocytes (all p<0.05). Conclusions Our replication study suggests that variants in 17q21 are significantly associated with risk of adult-onset asthma and gene expression in a Chinese Han population.